Residual stress, thermomechanics & infrared imaging, hybrid techniques and inverse problems. Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics. Volume 9 : (2016) - Unknown
No abstract available